2014
DOI: 10.1080/07391102.2014.951688
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and modelling studies suggest that the SKICH domains from different protein families share a common Ig-like fold but harbour substantial structural variations

Abstract: TAX1BP1 is a pleiotropic multi-domain protein involved in many important biological processes such as signal transduction, cell growth and apoptosis, transcriptional coactivation, membrane trafficking, neurotransmission and autophagy. The N-terminus of TAX1BP1 contains a SKICH domain implicated in autophagy. SKICH domains are also present in four other proteins including NDP52, CALCOCO1, SKIP and PIPP. The SKICH domains of SKIP and PIPP mediate plasma membrane localisation. The functions of the SKICH domains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…The protein G beads were washed by 1× PBS three times, and eluted by 0.1 M glycine-HCL, pH=2.8. The elution was dialyzed in 4 L 1 × PBS overnight 30,31,60 . The concentration of the iPDL1 protein was determined using BSA Assay kit (Thermo, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The protein G beads were washed by 1× PBS three times, and eluted by 0.1 M glycine-HCL, pH=2.8. The elution was dialyzed in 4 L 1 × PBS overnight 30,31,60 . The concentration of the iPDL1 protein was determined using BSA Assay kit (Thermo, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The ~100 amino-acid SKICH domain (for SKIP carboxy-homology domain) has an Ig-like βbarrel structure and a molecular surface dominated by negatively charged regions which may interact with components of the plasma membrane (Yang et al, 2015). The SKICH domain and surrounding sequences present at the C-terminus of INPP5K mediates interactions with specific proteins and regulate intracellular localization (Gurung et al, 2003;Dong et al, 2018).…”
Section: Human and Mouse Inpp5k Protein Structure And Catalytic Activmentioning
confidence: 99%
“…Structural analysis of this domain showed a b-sandwich fold comprising nine antiparallel b-strands and two very short a-helices, organized in two sheets of four and three strands (von Muhlinen et al 2012;Yang et al 2014). Structural and homologous models of SKICH domains have showed that this domain has an Ig-like b-barrel structure (Yang et al 2015). Among SKICH domains, the SKIP SKICH domain has a molecular surface dominated by negatively charged regions (Yang et al 2015), which may interact with components of the PM.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and homologous models of SKICH domains have showed that this domain has an Ig-like b-barrel structure (Yang et al 2015). Among SKICH domains, the SKIP SKICH domain has a molecular surface dominated by negatively charged regions (Yang et al 2015), which may interact with components of the PM. This b-barrel structure is found in outer membrane proteins of Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%